A comparative study to assess structure–properties relationships in (acrylonitrile butadiene rubber)‐based composites: Recycled microfillers versus nanofillers. Issue 1 (23rd March 2015) - Ebrahimi Jahromi, Hamid Reza; Bakhshandeh, Golam Reza; Ebrahimi Jahromi, Ali; Saeb, Mohammad Reza; Ahmadi, Zahed; Pakdel, Amir Saeid
Abstract : This paper reports on the reinforcing effects of different types of fillers, namely, nanoclay (NC), micron size calcium carbonate (MCC), and micron size recycled powder coating waste (MPCW), on the ultimate properties of acrylonitrile butadiene rubber (NBR) compounds. The microcomposites and nanocomposites were characterized by X‐ray diffraction and scanning electron microscopy, implying enlargement of d ‐spacing of NC or intercalation of NBR chains and formation of exfoliated structure, while some agglomerates of MCC were detected. Curing characteristics of the studied composites showed that incorporation of the fillers into the NBR, in particular the NC, causes an increase in the torque, indicating a higher degree of crosslinking. Furthermore, different from micron size MPCW and MCC, the NC accelerated the vulcanization reaction. It was also found that the use of NC and MPCW results in a remarkable increase in the mechanical and rheological properties compared with pure NBR. All in all, variations in the aforementioned criteria were attributable to the extent of matrix/filler interaction reflected by scanning electron micrographs. The correlation established between the microstructure and characteristics of the prepared NBR composites can shed some light on how to develop composites with enhanced properties by incorporating waste materials into the polymers. J. VINYL ADDIT. TECHNOL., 23:13–20, 2017. © 2015 Society of Plastics Engineers